Coated glass, laminated glass and preparation method of coated glass

By using ceramic ZnSnO3 layer as the intermediate layer in coated glass, the problem of poor mechanical properties of the coated glass film layer is solved, and higher mechanical properties and higher yields are achieved.

CN119707315AActive Publication Date: 2025-03-28FUYAO GLASS IND GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411842863.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing coated glass has poor mechanical properties, is easily scratched by hard objects, and has a low yield.

Method used

The ceramic ZnSnO3 layer is used as the intermediate layer of the coating structure, and its density and hardness are improved through magnetron sputtering technology, thereby improving the overall hardness of the coating structure.

Benefits of technology

The mechanical properties of coated glass are improved, making it have sufficient hardness to resist various scratches during deep processing, and the yield rate is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707315A_ABST
    Figure CN119707315A_ABST
Patent Text Reader

Abstract

The invention provides coated glass, laminated glass and a preparation method of the coated glass, the coated glass comprises a first substrate and a coating structure, the coating structure is arranged on the first substrate, the coating structure comprises at least two functional laminated layers and at least one middle layer, the at least two functional laminated layers are sequentially laminated on the first substrate, and the at least one middle layer is arranged on the first substrate. In the direction deviating from the first substrate, each functional lamination layer comprises a first dielectric layer, a metal layer and a second dielectric layer which are sequentially laminated, the metal layer is arranged between the first dielectric layer and the second dielectric layer, an intermediate layer is arranged between two adjacent functional lamination layers, at least one intermediate layer comprises a ceramic ZnSnO3 layer, the refractive index n value of the ceramic ZnSnO3 layer is 1.95-2.05, and the refractive index n value of the ceramic ZnSnO3 layer is 1.95-2.05. And the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0 * 10 <-3 >-7.0 * 10 <-3 >. The coated glass provided by the invention has higher mechanical properties and sufficient hardness to resist various scratches in the deep processing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass technology, and in particular to a method for preparing coated glass, laminated glass and coated glass. Background Art

[0002] Low-E glass has thermal properties such as energy saving, heat insulation, and sun shading, and is deeply loved by customers. It is mainly used as energy-saving glass for glass curtain walls and car windshields. Among them, low-E glass achieves thermal properties such as energy saving, heat insulation, and sun shading through a low-E coating structure. However, the mechanical properties of the film layer of the coating structure are currently poor, and it is easily scratched by hard objects, and the yield rate is not high in deep processing. Summary of the invention

[0003] The purpose of the embodiments of the present application is to provide a method for preparing coated glass, laminated glass and coated glass, wherein the coated glass has higher mechanical properties and sufficient hardness to resist various scratches during deep processing.

[0004] The present application provides a coated glass, the coated glass comprising:

[0005] a first substrate; and

[0006] The coating structure is arranged on the first substrate, the coating structure includes at least two functional stacks and at least one intermediate layer, the at least two functional stacks are sequentially stacked on the first substrate, and in a direction away from the first substrate, each functional stack includes a first dielectric layer, a metal layer and a second dielectric layer stacked in sequence, the metal layer is arranged between the first dielectric layer and the second dielectric layer, an intermediate layer is arranged between two adjacent functional stacks, and at least one intermediate layer includes a ceramic ZnSnO3 layer, wherein the refractive index n value of the ceramic ZnSnO3 layer is 1.95-2.05, and the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0*10 -3 ~7.0*10 -3 .

[0007] The embodiment of the present application provides a coated glass, which uses a ceramic ZnSnO3 layer as the middle layer of the coating structure. On the one hand, the ceramic ZnSnO3 layer has good thermal ductility of metal oxides, and can be used as an intermediate layer in the coating structure to connect the metal layer and the non-metallic material, so that the coating structure will not crack during the heat treatment process due to the large difference in thermal expansion coefficient between the metal layer and the non-metallic layer. On the other hand, compared with other materials, the refractive index n value is 1.95~2.05, and the extinction coefficient k value is 2.0*10 -3 ~7.0*10 -3The ceramic ZnSnO3 layer has a high density, which can improve the film hardness of the ceramic ZnSnO3 layer, thereby helping to improve the film hardness of the coating structure. When the ceramic ZnSnO3 layer is used as an intermediate layer, it can improve the overall hardness of the coating structure. On the one hand, it solves the problem of poor film mechanical properties of the existing coating structure, and on the other hand, it makes the coated glass have higher mechanical properties, so that it has sufficient hardness to resist various scratches during deep processing.

[0008] In a possible implementation, the coating structure further includes an adhesion layer and a protective layer, the adhesion layer is disposed on the surface of the first substrate, and the at least two functional stacks are disposed on a side of the adhesion layer away from the first substrate.

[0009] In a possible implementation, the adhesion layer includes at least one of a SiAlZrNx layer, a ZrOx layer, a NbOx layer, a SiNx layer, a ZnSnOx layer, a SiZrNx layer and a ceramic ZnSnO3 layer.

[0010] In a possible implementation, the coating structure further includes a protective layer, which is disposed on a side of the at least two functional stacks away from the adhesion layer, and at least one of the adhesion layer and the protective layer includes a ceramic ZnSnO3 layer.

[0011] In a possible embodiment, along the direction away from the first substrate, the protective layer includes an inner protective layer and an outer protective layer, the inner protective layer is arranged on the side of at least two functional stacks away from the adhesion layer, the outer protective layer is arranged on the side of the inner protective layer away from the at least two functional stacks, and the inner protective layer includes a ceramic ZnSnO3 layer.

[0012] In a possible embodiment, the inner protective layer includes a first protective layer and a second protective layer, the first protective layer is arranged on the side of at least two functional stacks away from the adhesion layer, and the second protective layer is arranged between the first protective layer and the outer protective layer, wherein the second protective layer is a ceramic ZnSnO3 layer.

[0013] In a possible implementation, the material of the first protective layer is selected from oxides of at least one element among Zn, Mg, Sn, Ti, Nb, and Zr.

[0014] In a possible implementation, the outer protective layer includes at least one of a SiAlZrNx layer, a SiZrNx layer, a ZrOx layer, a SiNx layer, a SiZrOx layer, and a SiAlZrOx layer.

[0015] In a possible embodiment, the first dielectric layer includes at least one of an AZO layer, a Ti alloy layer, a NbOx layer, a TiOx layer, a NiCr layer, a NiCrOx layer, a ZnAlOx layer, a ZnOx layer and a SnOx layer, and the second dielectric layer includes at least one of an AZO layer, a Ti alloy layer, a NbOx layer, a TiOx layer, a NiCr layer, a NiCrOx layer, a ZnAlOx layer, a ZnOx layer and a SnOx layer.

[0016] In a possible implementation manner, the material of the metal layer includes any one of Ag, Au, Cu and Al or a metal alloy.

[0017] In a possible embodiment, there are two functional stacks, the two functional stacks include a first functional stack and a second functional stack, there is one intermediate layer, the intermediate layer is a first intermediate layer, the coating structure also includes a protective layer, the protective layer includes a first protective layer, a second protective layer and an outer protective layer, the coating structure includes an adhesion layer, a first functional stack, a first intermediate layer, a second functional stack, a first protective layer, a second protective layer and an outer protective layer which are stacked in sequence, and the first intermediate layer includes a ceramic ZnSnO3 layer.

[0018] In one possible embodiment, there are three functional stacks, which include a first functional stack, a second functional stack and a third functional stack, there are two intermediate layers, which include a first intermediate layer and a second intermediate layer, the coating structure also includes a protective layer, which includes a first protective layer, a second protective layer and an outer protective layer, and the coating structure includes an adhesion layer, a first functional stack, a first intermediate layer, a second functional stack, a second intermediate layer, a third functional stack, a first protective layer, a second protective layer and an outer protective layer stacked in sequence, and the first intermediate layer and the second intermediate layer both include a ceramic ZnSnO3 layer.

[0019] In a possible implementation manner, the pencil hardness of the ceramic ZnSnO3 layer is ≥5H, and the pencil hardness of the coated glass after heat treatment is ≥7H.

[0020] An embodiment of the present application further provides a laminated glass, comprising a second substrate, an adhesive layer and the coated glass as described above, wherein the adhesive layer is bonded between the second substrate and the coating structure of the coated glass.

[0021] The present application also provides a method for preparing coated glass, comprising:

[0022] providing a first substrate;

[0023] A coating structure is prepared on a first substrate, the coating structure comprising at least two functional stacks and at least one intermediate layer, the at least two functional stacks are sequentially stacked on the first substrate, along a direction away from the first substrate, each functional stack comprises a first dielectric layer, a metal layer, and a second dielectric layer sequentially stacked, the metal layer is arranged between the first dielectric layer and the second dielectric layer, an intermediate layer is arranged between two adjacent functional stacks, at least one intermediate layer comprises a ceramic ZnSnO3 layer, wherein the refractive index n value of the ceramic ZnSnO3 layer is 1.95-2.05, and the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0*10 -3 ~7.0*10 -3 .

[0024] In a possible embodiment, the step of preparing a coating structure on the first substrate includes the step of preparing a ceramic ZnSnO3 layer: the target material is configured as a ZTO target material, and a high-power pulsed magnetron sputtering power supply is used as a target power supply to magnetron sputter the ZTO target material to obtain a ceramic ZnSnO3 layer.

[0025] In a possible implementation manner, the sputtering rate of magnetron sputtering is 2.1 nm*m / (min*kW) to 2.8 nm*m / (min*kW).

[0026] In one possible embodiment, the peak power density of magnetron sputtering is 14.47 W / cm 2 ~58.43W / cm 2 , the duty cycle is 5%~18%, and the pulse width is 30μs~60μs.

[0027] In a possible implementation manner, the mass ratio of Zn:Sn in the ZTO target is 40:60 to 60:40. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 A schematic diagram of the cross-sectional structure of the laminated glass provided in an embodiment of the present application;

[0030] Figure 2 for Figure 1 The schematic diagram of the cross-sectional structure of the coated glass in the laminated glass in the first embodiment is shown;

[0031] Figure 3 for Figure 1The schematic diagram of the cross-sectional structure of the coated glass in the laminated glass in the second embodiment is shown;

[0032] Figure 4 for Figure 1 The schematic diagram of the cross-sectional structure of the coated glass in the laminated glass in the third embodiment;

[0033] Figure 5 A schematic diagram of the preparation process of coated glass provided in an embodiment of the present application. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0035] For ease of understanding, the terms involved in the embodiments of the present application are first explained.

[0036] And / or: It is just a way to describe the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone.

[0037] The value of x in the chemical formula: if it is clearly defined, it shall be within the defined range. If it is not clearly defined, it can be determined based on the deposition in a stoichiometric, substoichiometric or superstoichiometric manner in the magnetron sputtering process.

[0038] Heat treatment: high temperature heat treatment of at least 500°C, such as the self-weight bending process or press bending process for the production of automotive glass.

[0039] See also Figure 1 , Figure 1 This is a schematic diagram of the cross-sectional structure of the laminated glass 1000 provided in an embodiment of the present application.

[0040] The embodiment of the present application provides a laminated glass 1000, which can be applied to vehicles, doors and windows, glass curtain walls, etc. For example, when the laminated glass 1000 is applied to a vehicle, the laminated glass 1000 can be the front windshield, rear windshield, skylight glass, side window glass, etc. of the vehicle.

[0041] Specifically, the laminated glass 1000 includes a coated glass 100, an adhesive layer 300 and a second substrate 500. The adhesive layer 300 is bonded between the coated glass 100 and the second substrate 500. In the embodiment of the present application, the pencil hardness of the coated glass 100 after heat treatment is ≥7H, that is, the pencil hardness of the film surface of the coated glass 100 under the pencil hardness test after heat treatment is ≥7H. Among them, the coated glass 100 includes a first substrate 110 and a coating structure 130, and the coating structure 130 is arranged on at least one side of the first substrate 110 along the thickness direction. In the following embodiments, the coating structure 130 is arranged on one side of the first substrate 110 along the thickness direction as an example for description. The adhesive layer 300 is bonded between the coating structure 130 of the coated glass 100 and the second substrate 500, so as to achieve the bonding of the adhesive layer 300 between the coated glass 100 and the second substrate 500.

[0042] Exemplarily, the first substrate 110 and the second substrate 500 can both be transparent glass or ultra-white glass (white glass). Among them, the coating structure 130 is a low-emissivity film layer (Low-E film layer) to achieve the properties of heat insulation and sunshade of the coated glass 100. The bonding layer 300 can be used to improve the structural strength of the laminated glass 1000 so that it meets the safety standards and regulatory requirements of more scenarios. Exemplarily, the material of the bonding layer 300 can be polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), thermoplastic polyurethane elastomer (TPU) or ionic polymer film (SGP), etc. Exemplarily, the bonding layer 300 includes at least one film layer. For example, the bonding layer 300 can be one layer, two layers, three layers, four layers, etc., and the embodiment of the present application does not limit the number of layers of the bonding layer 300.

[0043] See also Figure 2 , Figure 2 for Figure 1 The cross-sectional structure diagram of the coated glass 100 in the laminated glass 1000 in the first embodiment is shown.

[0044] In the embodiment of the present application, the coating structure 130 includes an adhesion layer 10, at least two functional stacks 30, at least one intermediate layer 50 and a protective layer 70. The adhesion layer 10 is disposed on the surface of the first substrate 110, at least two functional stacks 30 are sequentially stacked on the first substrate 110 and disposed on the side of the adhesion layer 10 away from the first substrate 110, an intermediate layer 50 is disposed between two adjacent functional stacks 30, and the protective layer 70 is disposed on the side of at least two functional stacks 30 away from the adhesion layer 10. Among them, the coating structure 130 has a low-emissivity effect, so that the coated glass 100 has the properties of heat insulation and sunshade.

[0045] In the coating structure 130 of the coated glass 100 of the first embodiment, three functional stacks 30 and two intermediate layers 50 are used for illustration. The three functional stacks 30 include a first functional stack 31, a second functional stack 32 and a third functional stack 33, and the two intermediate layers 50 include a first intermediate layer 51 and a second intermediate layer 52. At this time, the coating structure 130 specifically includes an adhesion layer 10, a first functional stack 31, a first intermediate layer 51, a second functional stack 32, a second intermediate layer 52, a third functional stack 33 and a protective layer 70 which are stacked in sequence. It can be understood that the functional stack 30 can be two, three, four, etc., and the embodiment of the present application does not limit the number of the functional stack 30, and the intermediate layer 50 can be one, two, three, etc., and the embodiment of the present application does not limit the number of the intermediate layer 50.

[0046] Specifically, the adhesion layer 10 is used to improve the adhesion of the coating structure 130 on the first substrate 110. Exemplarily, the adhesion layer 10 includes at least one of a SiAlZrNx layer, a ZrOx layer, a NbOx layer, a SiNx layer, a ZnSnOx layer, and a SiZrNx layer. It is understandable that the x value in the chemical formula of each material that can be selected in the above-mentioned adhesion layer 10 can be the same or different. Exemplarily, 1≤x≤3. Exemplarily, the thickness of the adhesion layer 10 is 10nm to 40nm. For example, the thickness of the adhesion layer 10 can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, etc.

[0047] In the direction away from the first substrate 110, each functional stack 30 includes a first dielectric layer 301, a metal layer 303, and a second dielectric layer 305 which are stacked in sequence, and the metal layer 303 is disposed between the first dielectric layer 301 and the second dielectric layer 305. Exemplarily, in the coating structure 130 of the first embodiment, the first functional stack 31, the second functional stack 32, and the third functional stack 33 all include the first dielectric layer 301, the metal layer 303, and the second dielectric layer 305. In each functional stack 30, the first dielectric layer 301 faces the first substrate 110, the metal layer 303 is disposed on the side of the first dielectric layer 301 away from the first substrate 110, and the second dielectric layer 305 is disposed on the side of the metal layer 303 away from the first dielectric layer 301.

[0048] In each functional stack 30 , the first dielectric layer 301 and the second dielectric layer 305 can be used to protect the metal layer 303 from damage by alkali metal ions, oxygen, etc. The first dielectric layer 301 can also serve as a crystallization seed layer of the metal layer 303 to improve the deposition density of the metal layer 303 .

[0049] Exemplarily, the first dielectric layer 301 includes at least one of an AZO layer, a Ti alloy layer, a NbOx layer, a TiOx layer, a NiCr layer, a NiCrOx layer, a ZnAlOx layer, a ZnOx layer, and a SnOx layer. It is understood that the x value in the chemical formula of each material that can be selected in the first dielectric layer 301 can be the same or different. Exemplarily, 1≤x≤3. Exemplarily, the thickness of the first dielectric layer 301 is 5nm to 30nm. For example, the thickness of the first dielectric layer 301 can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, etc. Exemplarily, the material of the metal layer 303 includes any one of Ag, Au, Cu, and Al metal or metal alloy. For example, the material of the metal layer 303 can be Ag, AgCu alloy, AgIn alloy, etc. Exemplarily, the thickness of the metal layer 303 is 5nm to 20nm. For example, the thickness of the metal layer 303 can be 5nm, 10nm, 15nm, 20nm, etc. Exemplarily, the second dielectric layer 305 includes at least one of an AZO layer, a Ti alloy layer, a NbOx layer, a TiOx layer, a NiCr layer, a NiCrOx layer, a ZnAlOx layer, a ZnOx layer, and a SnOx layer. It is understood that the x value in the chemical formula of each material that can be selected in the second dielectric layer 305 can be the same or different. Exemplarily, 1≤x≤3. Exemplarily, the thickness of the second dielectric layer 305 is 5nm to 30nm. For example, the thickness of the second dielectric layer 305 can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, etc.

[0050] In the embodiment of the present application, at least one intermediate layer 50 includes a ceramic ZnSnO3 layer, and the ceramic ZnSnO3 layer is disposed between two adjacent functional stacks 30, so that the intermediate layer 50 is disposed between two adjacent functional stacks 30. The refractive index n value of the ceramic ZnSnO3 layer is 1.95 to 2.05, and the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0*10 -3 ~7.0*10 -3 For example, the refractive index n value of the ceramic ZnSnO3 layer can be 1.95, 1.96, 1.97, 1.98, 1.99, 2.00, 2.01, 2.02, 2.03, 2.04, 2.05, etc. For example, the extinction coefficient k value of the ceramic ZnSnO3 layer can be 2.0*10 -3 , 3.0*10 -3 , 4.0*10 -3 , 5.0*10 -3 , 6.0*10 -3 ,7.0*10 -3In the embodiment of the present application, the pencil hardness of the ceramic ZnSnO3 layer is ≥5H, that is, the pencil hardness of the film surface of the ceramic ZnSnO3 layer under the pencil hardness test is ≥5H.

[0051] Exemplarily, the thickness of the intermediate layer 50 is 30nm to 75nm. For example, the thickness of the intermediate layer 50 can be 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, etc. In the first embodiment, the first intermediate layer 51 and the second intermediate layer 52 are both ceramic ZnSnO3 layers, the thickness of the first intermediate layer 51 is 30nm to 75nm, and the thickness of the second intermediate layer 52 is 30nm to 75nm.

[0052] The protective layer 70 is disposed on the outermost functional stack 30 away from the first substrate 110 among the at least two functional stacks 30. The protective layer 70 is used to provide protection for the coating structure 130 to prevent the coating structure 130 from being corroded and mechanically damaged. The protective layer 70 includes at least one film layer. For example, the protective layer 70 can have one layer, two layers, three layers, four layers, etc., and the embodiment of the present application does not limit the number of film layers of the protective layer 70.

[0053] In the first embodiment, the protective layer 70 includes an inner protective layer 71 and an outer protective layer 73. The inner protective layer 71 is disposed on the side of at least two functional stacks 30 away from the first substrate 110, and the outer protective layer 73 is disposed on the side of the inner protective layer 71 away from the at least two functional stacks 30. Among them, the inner protective layer 71 includes at least one film layer. In the first embodiment, the inner protective layer 71 is illustrated as having two film layers. Specifically, the protective layer 70 of the first embodiment has three layers, and the inner protective layer 71 includes a first protective layer 711 and a second protective layer 712. At this time, the protective layer 70 includes a first protective layer 711, a second protective layer 712 and an outer protective layer 73 stacked in sequence. It can be understood that in other embodiments, the protective layer 70 may also have two layers, and the inner protective layer 71 may also have a film layer, which is the first protective layer 711. At this time, the protective layer 70 includes a first protective layer 711 and an outer protective layer 73 stacked in sequence.

[0054] Exemplarily, the material of the first protective layer 711 is selected from the oxide of at least one element of Zn, Mg, Sn, Ti, Nb, and Zr. For example, the material of the first protective layer 711 is TiOx, 1≤x≤3. Exemplarily, the thickness of the first protective layer 711 is 0 to 25 nm. For example, the thickness of the first protective layer 711 can be 0 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, etc. Exemplarily, the second protective layer 712 can be a ZnSnOx layer, 1≤x≤3. Exemplarily, the thickness of the second protective layer 712 is 0 to 25 nm. For example, the thickness of the second protective layer 712 can be 0 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, etc. Exemplarily, the outer protective layer 73 can be at least one of a SiAlZrNx layer, a SiZrNx layer, a ZrOx layer, a SiNx layer, a SiZrOx layer, and a SiAlZrOx layer. It is understandable that the x values ​​in the chemical formulas of the materials that can be selected in the outer protective layer 73 can be the same or different. Exemplarily, 1≤x≤3. Exemplarily, the thickness of the outer protective layer 73 is 5 to 70 nm. For example, the thickness of the outer protective layer 73 can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, etc. It should be noted that the x values ​​in the chemical formulas of the materials that can be selected in the outer protective layer 73, the second protective layer 712, the first protective layer 711, the second dielectric layer 305, the first dielectric layer 301, and the adhesion layer 10 can be the same or different, and the present application does not impose any restrictions on this.

[0055] In order to solve the problem of poor mechanical properties of the film layer of the coating structure, the hard material SiC can be used as the outermost protective layer to protect the film layer from being damaged during processing. It is also possible to select hard transparent ceramic materials ZrO2 and Nb2O5 layers as the bottom dielectric layer, and use hard Si3N4 and ZrO2 layers as the outermost protective layer to make the film layer resistant to processing. However, these protective layer materials only increase the hardness of the innermost or outermost layer of the coating structure, and do not increase the overall hardness of the coating structure, and are not enough to fully guarantee the processing resistance of the coating structure.

[0056] In order to solve the above problems, the embodiment of the present application provides a coated glass 100, which uses a ceramic ZnSnO3 layer as the intermediate layer 50 of the coating structure 130. On the one hand, the ceramic ZnSnO3 layer has good thermal ductility of metal oxides, and can be used as the intermediate layer 50 in the coating structure 130 to link the metal layer 303 and the non-metallic material such as the non-metallic protective layer SiNx, so that the coating structure 130 will not crack during the heat treatment process due to the large difference in thermal expansion coefficients of the metal layer 303 and the non-metallic layer. On the other hand, compared with other materials, the refractive index n value is 1.95~2.05, and the extinction coefficient k value is 2.0*10 -3 ~7.0*10 -3 The ceramic ZnSnO3 layer has a high density, which can improve the film hardness of the ceramic ZnSnO3 layer, thereby helping to improve the film hardness of the coating structure 130, so that the ceramic ZnSnO3 layer can improve the overall hardness of the coating structure 130 when used as an intermediate layer. On the one hand, it solves the problem of poor film mechanical properties of the existing coating structure, and on the other hand, it makes the coated glass 100 have higher mechanical properties, so that it has sufficient hardness to resist various scratches during deep processing.

[0057] See also Figure 3 , Figure 3 for Figure 1 The cross-sectional structure diagram of the coated glass 100 in the laminated glass 1000 is shown in the second embodiment.

[0058] In the coating structure 130 of the coated glass 100 of the second embodiment, there are two functional stacks 30 and one intermediate layer 50. The two functional stacks 30 include a first functional stack 31 and a second functional stack 32, and one intermediate layer 50 is a first intermediate layer 51. At this time, the coating structure 130 specifically includes an adhesion layer 10, a first functional stack 31, a first intermediate layer 51, a second functional stack 32 and a protective layer 70 which are stacked in sequence. The first functional stack 31 and the second functional stack 32 both include a first dielectric layer 301, a metal layer 303 and a second dielectric layer 305.

[0059] In the coating structure 130 of the second embodiment, the first intermediate layer 51 is a ceramic ZnSnO3 layer, and the protective layer 70 includes a first protective layer 711, a second protective layer 712 and an outer protective layer 73. The adhesion layer 10, the first functional stack 31 and the second functional stack 32 can be selected with reference to the first embodiment.

[0060] See also Figure 4 , Figure 4 for Figure 1 The cross-sectional structure diagram of the coated glass 100 in the laminated glass 1000 is shown in the third embodiment.

[0061] In the coating structure 130 of the coated glass 100 of the third embodiment, there are four functional stacks 30 and three intermediate layers 50. The four functional stacks 30 include a first functional stack 31, a second functional stack 32, a third functional stack 33 and a fourth functional stack 34. The three intermediate layers 50 include a first intermediate layer 51, a second intermediate layer 52 and a third intermediate layer 53. At this time, the coating structure 130 specifically includes an adhesion layer 10, a first functional stack 31, a first intermediate layer 51, a second functional stack 32, a second intermediate layer 52, a third functional stack 33, a third intermediate layer 53, a fourth functional stack 34 and a protective layer 70 which are stacked in sequence. The first functional stack 31, the second functional stack 32, the third functional stack 33 and the fourth functional stack 34 all include a first dielectric layer 301, a metal layer 303 and a second dielectric layer 305.

[0062] In the coating structure 130 of the third embodiment, the first intermediate layer 51, the second intermediate layer 52 and the third intermediate layer 53 are all ceramic ZnSnO3 layers, and the protective layer 70 includes a first protective layer 711, a second protective layer 712 and an outer protective layer 73. The adhesion layer 10, the first functional stack 31, the second functional stack 32, the third functional stack 33 and the fourth functional stack 34 can all be selected with reference to the first embodiment.

[0063] Combined with reference Figures 2 to 4 In the coating structure 130 of the coated glass 100 of some embodiments, at least one of the adhesion layer 10 and the protective layer 70 includes a ceramic ZnSnO3 layer to further improve the film hardness of the coating structure 130. For example, in the coating structure 130 of the first embodiment and the second embodiment, the adhesion layer 10 includes a ceramic ZnSnO3 layer, or the protective layer 70 includes a ceramic ZnSnO3 layer, or both the adhesion layer 10 and the protective layer 70 include a ceramic ZnSnO3 layer.

[0064] Among them, taking the coating structure 130 in the first embodiment, the second embodiment and the third embodiment as an example, the protective layer 70 includes an inner protective layer 71 and an outer protective layer 73. At this time, the inner protective layer 71 in the protective layer 70 includes a ceramic ZnSnO3 layer to avoid film defects when the ceramic ZnSnO3 layer is set as the outer protective layer 73, so that the coating structure 130 has a better film hardness. Exemplarily, in some specific embodiments, the second protective layer 712 in the inner protective layer 71 is a ceramic ZnSnO3 layer.

[0065] Combined with reference Figure 5 , Figure 5 The schematic diagram of the preparation process of the coated glass 100 provided in the embodiment of the present application is shown in FIG.

[0066] The embodiment of the present application also provides a method for preparing the coated glass 100, comprising:

[0067] S1. Provide a first substrate 110.

[0068] S2. Prepare a coating structure 130 on the first substrate 110. The coating structure 130 includes at least two functional stacks 30 and at least one intermediate layer 50. The at least two functional stacks 30 are sequentially stacked on the first substrate 110. In the direction away from the first substrate 110, each functional stack 30 includes a first dielectric layer 301, a metal layer 303, and a second dielectric layer 305 stacked in sequence. The metal layer 303 is arranged between the first dielectric layer 301 and the second dielectric layer 305. An intermediate layer 50 is arranged between two adjacent functional stacks 30. At least one intermediate layer 50 includes a ceramic ZnSnO3 layer, wherein the refractive index n value of the ceramic ZnSnO3 layer is 1.95-2.05, and the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0*10 -3 ~7.0*10 -3 .

[0069] In the embodiment of the present application, step S2 includes the step of preparing a ceramic ZnSnO3 layer: the target material is configured as a ZTO (zinc tin oxide) target material, and a high power pulse magnetron sputtering (HiPIMS) power supply is used as the target power supply to magnetron sputter the ZTO target material to obtain a ceramic ZnSnO3 layer. Exemplarily, the mass ratio of Zn:Sn in the ZTO target material is 40:60 to 60:40. For example, the mass ratio of Zn:Sn in the ZTO target material can be 40:60, 50:50, 52:48, 60:40, etc. Exemplarily, the sputtering rate of magnetron sputtering is 2.1nm*m / (min*kW) to 2.8nm*m / (min*kW), that is, the ceramic ZnSnO3 layer is sputtered at a sputtering rate of 2.1nm*m / (min*kW) to 2.8nm*m / (min*kW).

[0070] In some specific embodiments, the target material is a ceramic ZTO target material, a HiPIMS power source is used as the target power source, 1 to 5 double rotating cathodes are used, and magnetron sputtering is performed in a mixture of argon and oxygen at a pressure of 1.0×10-3mbar to 6.0×10-3mbar to deposit a ceramic ZnSnO3 layer. The peak power density of the magnetron sputtering is 14.47W / cm 2 ~58.43W / cm 2, the duty cycle is 5% to 18%, and the pulse width is 30us to 60us. For example, the peak power for magnetron sputtering is 130kW to 525kW, the voltage is 650V to 1000V, and the current is 200A to 525A. Wherein, the peak power density = peak power / area of ​​the sputtering target.

[0071] The sputtering targets of traditional magnetron sputtering technology mostly exist in an atomic state, and the material ionization rate is low. The high-power pulsed magnetron sputtering (HiPIMS) used in the embodiment of the present application is an emerging ionization magnetron sputtering technology. By reducing the duty cycle, the target is supplied with MW-level instantaneous high power (about 1000 times the power of ordinary magnetron sputtering) in a short pulse (10us~500us), so that the plasma density is increased by 2~3 orders of magnitude compared with traditional magnetron sputtering. The ionization rate of some targets is even as high as more than 70%, so that the prepared ceramic ZnSnO3 layer has the advantages of dense structure, smooth surface, and high film-base bonding. In the embodiment of the present application, the ceramic ZnSnO3 layer is a dense ZnSnO3 film layer obtained by sputtering a ZTO target and a small amount of O2. Because the compactness of the ZTO target material is improved, the film hardness of the ceramic ZnSnO3 layer is improved, and then the film hardness of the coating structure 130 is improved.

[0072] The following is a detailed description of the preparation process conditions and performance of the above-mentioned ceramic ZnSnO3 layer in combination with experiments. Referring to Tables 1 and 2, the traditional ZnSnO3 layer in Tables 1 and 2 represents a film layer deposited using ZnSn (zinc-tin alloy) as a target material and MF (medium frequency magnetron) power supply as a target material power supply. The ordinary ZnSnO3 layer represents a film layer deposited using ZTO (zinc-tin oxide) as a target material and MF (medium frequency magnetron) power supply as a target material power supply. The ceramic ZnSnO3 layer represents a film layer deposited using ZTO (zinc-tin oxide) as a target material and HiPIMS (high power pulsed magnetron sputtering) power supply as a target material power supply. Among them, the area of ​​the sputtering target in Table 1 is approximately 8800cm 2 ~8900cm 2 The peak power density of the ceramic ZnSnO3 layer prepared by magnetron sputtering is approximately 14.47W / cm 2 ~58.43W / cm 2 .

[0073] Table 1 Comparison of power process parameters of traditional ZnSnO3 layer, ordinary ZnSnO3 layer and ceramic ZnSnO3 layer.

[0074]

[0075]

[0076] Table 2 Comparison of sputtering rates of traditional ZnSnO3 layer, ordinary ZnSnO3 layer and ceramic ZnSnO3 layer

[0077]

[0078] It can be seen from Table 1 and Table 2 that the sputtering rate when preparing the traditional ZnSnO3 layer with ZnSn as the target material and MF (medium frequency magnetron) power supply as the target material power supply is low, approximately 0.5nm*m / (min*kW)~1.3nm*m / (min*kW). The sputtering rate when preparing the ordinary ZnSnO3 layer is 15.4%~53.8% higher than that of the traditional ZnSnO3 layer. The sputtering rate when preparing the ceramic ZnSnO3 layer is 5%~40% higher than that of the ordinary ZnSnO3 layer, and is 61.5%~115.4% higher than that of the traditional ZnSnO3 layer.

[0079] Generally speaking, when a certain material is deposited using a HiPIMS power supply, its sputtering rate is slightly lower than the sputtering rate when the same material is deposited using an MF power supply. This application study found that the opposite situation occurred when the ZTO material was sputtered using a HiPIMS power supply. This is because the ZTO material has poor conductivity and is difficult to ionize. It is difficult to completely ionize the ZTO target when using an MF power supply. During the sputtering process, problems such as unstable voltage, sparking of the target, and severe arcing alarms often occur. The embodiment of this application uses ZTO (zinc tin oxide) as the target material and a HiPIMS (high-power pulsed magnetron sputtering) power supply as the target power supply. The sputtering rate of the ceramic ZnSnO3 layer is significantly improved. The increase in the sputtering rate is beneficial to the application of the ceramic ZnSnO3 layer material, and can greatly save the costs of the cavity, cathode, power supply, molecular pump, etc. required for the application of the ceramic ZnSnO3 layer material.

[0080] In addition, it can be seen from Table 1 and Table 2 that the refractive index n value range of the traditional ZnSnO3 layer and the ordinary ZnSnO3 layer is relatively close, and the refractive index n value of the ceramic ZnSnO3 layer is slightly lower than that of the traditional ZnSnO3 layer and the ordinary ZnSnO3 layer. At the same time, the extinction coefficient k value of the ceramic ZnSnO3 layer is slightly higher than the extinction coefficient k value of the traditional ZnSnO3 layer and the ordinary ZnSnO3 layer. This is because the sputtering energy of the HiPIMS power supply is large, making the ceramic ZnSnO3 layer denser, and a small amount of bond energy in the ceramic ZnSnO3 layer is destroyed.

[0081] The following experiments are combined to measure the film strength of the above-mentioned traditional ZnSnO3 layer, ordinary ZnSnO3 layer and ceramic ZnSnO3 layer. Since the pencil hardness of the above-mentioned single layers of various materials is greater than 9H and cannot be properly compared, glass is used as a substrate, a metal soft layer is deposited on the surface of the glass substrate, and then the above-mentioned various material layers are deposited on the metal soft layer as a protective layer to test the protective strength of the protective layer on the metal soft layer. The results are shown in Table 3. Among them, the SiZrNx layer in Table 3 is a film layer deposited using MF (medium frequency magnetron) power supply as the target power supply. The substrate is ordinary white glass with a thickness of 2.1mm, and the metal soft layer is an example of an Ag single layer with a thickness of 13.04nm.

[0082] Table 3 Material test hardness of SiZrNx layer, traditional ZnSnO3 layer, ordinary ZnSnO3 layer and ceramic ZnSnO3 layer

[0083]

[0084]

[0085] As can be seen from Table 3, the metal soft layer in Experimental Group 1 is a 13.04nm Ag single layer, which is deposited on a 2.1mm ordinary white glass surface, and the measured pencil hardness is 4B. By comparing the pencil hardness test results of each protective layer material, it can be seen that the surface hardness of the film layer is ranked as follows: ceramic ZnSnO3 layer> ordinary ZnSnO3 layer> SiZrNx layer> traditional ZnSnO3 layer. The experimental results show that the pencil hardness of the ceramic ZnSnO3 layer is ≥5H, which is much higher than other protective layer materials, and is more suitable as the intermediate layer of the coating structure 130 than other materials.

[0086] The application of the ceramic ZnSnO 3 layer to the coating structure 130 is described in detail below in combination with comparative examples and specific examples.

[0087] Comparative Examples 1-3:

[0088] Comparative Examples 1-3 provide a coated glass, comprising a first substrate / adhesion layer / first functional stack / first intermediate layer / second functional stack / second intermediate layer / third functional stack / first protective layer / second protective layer / outer protective layer stacked in sequence. The first functional stack, the second functional stack and the third functional stack all include a first dielectric layer, a metal layer and a second dielectric layer.

[0089] Embodiment 1-5:

[0090] Embodiments 1-5 provide a coated glass 100, which is a specific example of the coated glass 100 of the first embodiment, and includes a first substrate 110 / adhesion layer 10 / first functional stack 31 / first intermediate layer 51 / second functional stack 32 / second intermediate layer 52 / third functional stack 33 / first protective layer 711 / second protective layer 712 / outer protective layer 73 stacked in sequence. The first functional stack 31, the second functional stack 32, and the third functional stack 33 all include a first dielectric layer 301, a metal layer 303, and a second dielectric layer 305.

[0091] The coated glass of comparative examples 1-3 and the coated glass 100 of embodiments 1-5 were taken, and the pencil hardness of the coated glass before and after heat treatment at 550°C to 720°C, and the test results of alcohol wiping were respectively shown in Tables 4 and 5. Among them, the traditional ZnSnO3 layer used in Tables 4 and 5 is recorded as ZnSnO3 (MF), the ordinary ZnSnO3 layer is recorded as ZTO (MF), and the ceramic ZnSnO3 layer is recorded as ZTO (HiPIMS).

[0092] Table 4 Structure and test results of coated glass of Comparative Examples 1-3 and Example 1

[0093]

[0094]

[0095] Table 5 Structure and test results of coated glass of Examples 2-5

[0096]

[0097]

[0098]

[0099] As can be seen from Tables 4 and 5, in the coating structure of the coated glass of Comparative Example 1, ZnSnO3 was deposited using MF power supply, and ZnSnO3 (MF) was obtained as the adhesion layer, the first intermediate layer, the second intermediate layer and the second protective layer. The pencil hardness test of the coating structure of Comparative Example 1 before and after the heat treatment was 3H / 4H respectively. In the coating structure of the coated glass of Comparative Example 2, ZTO was deposited using MF power supply, and ZTO (MF) was obtained as the adhesion layer, the first intermediate layer, the second intermediate layer and the second protective layer. The pencil hardness test of the coating structure of Comparative Example 2 before and after the heat treatment was 7H / 6H respectively. In the coating structure of the coated glass of Comparative Example 3, Si3N4 was deposited using MF power supply, and Si3N4 was obtained as the adhesion layer, the first intermediate layer, the second intermediate layer and the second protective layer. The pencil hardness test of the coating structure of Comparative Example 3 before and after the heat treatment was 6H / 3H respectively. It can be seen that the coating structure of the coated glass of Comparative Examples 1-3 has a relatively low film hardness before and after the heat treatment. Among them, the hardness of the film layer of the coating structure of comparative example 3 after heat treatment is significantly reduced, indicating that the coating structure of comparative example 3 cannot meet the use requirements of the self-weight bending process or the press bending process for producing automotive glass.

[0100] By comparing Examples 1-5 and Comparative Examples 1-3, the coating structure 130 in the coated glass 100 of Examples 2-5 has a high pencil hardness before and after the heat treatment, and can meet the use requirements of the self-weight bending process or the press bending process of the production of automobile glass. In addition, the square resistance R of the coating structure 130 of Examples 1-5 can be reduced after the high-temperature heat treatment, and the alcohol wiping before and after the high-temperature heat treatment meets the requirements, indicating that the film system design of the coating structure 130 of Examples 1-5 is reasonable.

[0101] Among them, by comparing Examples 1-5 and Comparative Example 1, it can be seen that compared with the coating structure of Comparative Example 1, in Example 5, the ZTO (HiPIMS) (i.e., ceramic ZnSnO3 layer) obtained by depositing ZTO target material using HiPIMS power supply is used as the first intermediate layer 51 and the second intermediate layer 52, and the pencil hardness test of the obtained coating structure 130 before / after heat treatment is 9H / 8H respectively, and the overall film hardness of the coating structure 130 is improved. In Example 4, the ceramic ZnSnO3 layer is used as the adhesion layer 10, the first intermediate layer 51 and the second intermediate layer 52, and the pencil hardness test of the obtained coating structure 130 before / after heat treatment is 9H / 8H respectively, and the overall film hardness of the coating structure 130 is improved. In Example 3, the ceramic ZnSnO3 layer is used as the first intermediate layer 51, the second intermediate layer 52 and the second protective layer 712 in the inner protective layer 71, and the pencil hardness test of the obtained coating structure 130 before / after heat treatment is 9H / 9H respectively, and the overall film hardness of the coating structure 130 is improved. In Example 2, a ceramic ZnSnO3 layer is used as the adhesion layer 10, the first intermediate layer 51, the second intermediate layer 52 and the second protective layer 712 in the inner protective layer 71. The pencil hardness test of the obtained coating structure 130 before / after heat treatment is both >9H, and the overall film hardness of the coating structure 130 is improved.

[0102] The experimental results show that the instantaneous high power supplied by the HiPIMS power supply to the ZTO target in the embodiment of the present application not only promotes the ionization of the ZTO target to increase the sputtering rate, but also the prepared ZTO (HiPIMS) film (i.e., the ceramic ZnSnO3 layer) has the advantages of dense structure and smooth surface. The use of the film-coated structure 130 as an intermediate layer can improve the overall hardness of the film-coated structure 130, so that the film-coated structure 130 has sufficient hardness to cope with various scratch challenges during deep processing. In addition, by comparing Examples 2-3 and Example 5, it can be seen that at least one of the adhesion layer 10 and the protective layer 70 in the film-coated structure 130 uses a ceramic ZnSnO3 layer, which can further improve the overall hardness of the film-coated structure 130.

[0103] In addition, by comparing Example 1 and Example 2, the difference between the coating structure of Example 1 and Example 2 is that the outer protective layer 73 in Example 1 is a ceramic ZnSnO3 layer, and the pencil hardness test results of the coating structure of Example 1 before / after heat treatment are 6H / 7H respectively, which are slightly lower than the pencil hardness test results of the coating structure 130 of Example 2 before / after heat treatment. This is because the instantaneous high power supplied by the HiPIMS power supply to the ZTO target may cause a small amount of defects inside the film layer of the coating structure. When the ceramic ZnSnO3 layer is used as the outermost outer protective layer 73, it may react with O2 and water molecules in the air to affect the performance of the film layer. Therefore, in some preferred embodiments, the ceramic ZnSnO3 film layer is not provided on the outer protective layer 73.

[0104] Comparative Example 4:

[0105] Comparative Example 4 provides a coated glass, comprising a first substrate / adhesion layer / first functional stack / first intermediate layer / second functional stack / first protective layer / second protective layer / outer protective layer stacked in sequence, wherein the first functional stack and the second functional stack both include a first dielectric layer, a metal layer, and a second dielectric layer.

[0106] Embodiment 6-8:

[0107] Embodiments 6-8 provide a coated glass 100, which is a specific example of the coated glass 100 of the second embodiment, and includes a first substrate 110 / adhesion layer 10 / first functional stack 31 / first intermediate layer 51 / second functional stack 32 / first protective layer 711 / second protective layer 712 / outer protective layer 73 stacked in sequence. The first functional stack 31 and the second functional stack 32 both include a first dielectric layer 301, a metal layer 303, and a second dielectric layer 305.

[0108] The coated glass of comparative example 4 and the coated glass 100 of embodiments 6-8 were taken to measure the pencil hardness of the coated glass before and after heat treatment at 550°C to 720°C, and the test results of alcohol wiping are shown in Table 6. Among them, the traditional ZnSnO3 layer used in Table 6 is recorded as ZnSnO3 (MF), the ordinary ZnSnO3 layer is recorded as ZTO (MF), and the ceramic ZnSnO3 layer is recorded as ZTO (HiPIMS).

[0109] Table 6 Structure and test results of coated glass of Comparative Example 4 and Examples 6-8

[0110]

[0111]

[0112] As can be seen from Table 6, in the coating structure of the coated glass of Comparative Example 4, MF power is used to deposit ZnSnO3, and the obtained ZnSnO3 (MF) is used as the adhesion layer, the first intermediate layer and the second protective layer. The pencil hardness test of the coating structure of Comparative Example 4 before / after heat treatment is 4H / 5H respectively, and the film hardness is relatively low. In Examples 6-8, HiPIMS power is used to supply instantaneous high power to the ZTO target, which not only promotes the ionization of the ZTO target to increase the sputtering rate, but also the prepared ZTO (HiPIMS) (i.e., ceramic ZnSnO3 layer) has the advantages of dense structure and smooth surface. Among them, in Example 6, a ceramic ZnSnO3 layer is used as the adhesion layer 10, the first intermediate layer 51 and the second protective layer 712, in Example 7, a ceramic ZnSnO3 layer is used as the adhesion layer 10 and the first intermediate layer 51, and in Example 8, a ceramic ZnSnO3 layer is used as the first intermediate layer 51 and the second protective layer 712, and the obtained coating structure 130 has a higher film hardness.

[0113] The experimental results show that the use of the ceramic ZnSnO3 layer as the first intermediate layer 51 can improve the overall hardness of the coating structure 130, and as the adhesion layer 10 and / or the second protective layer 712 can further improve the overall hardness of the coating structure 130, so that the coating structure 130 has sufficient hardness to cope with various scratch challenges during deep processing. Among them, when the ceramic ZnSnO3 layer is used as the adhesion layer 10, the first intermediate layer 51 and the second protective layer 712 at the same time, the pencil hardness test of the coating structure 130 before / after heat treatment of Example 6 is respectively>9H / >9H, and the coating structure 130 has sufficient hardness to cope with various scratch challenges during deep processing.

[0114] Comparative Example 5:

[0115] Comparative Example 5 provides a coated glass, comprising a first substrate / adhesion layer / first functional stack / first intermediate layer / second functional stack / second intermediate layer / third functional stack / third intermediate layer / fourth functional stack / first protective layer / second protective layer stacked in sequence. The first functional stack, the second functional stack, the third functional stack and the fourth functional stack all include a first dielectric layer, a metal layer and a second dielectric layer.

[0116] Embodiment 9-11:

[0117] Embodiments 9-11 provide a coated glass 100, which is a specific example of the coated glass 100 of the third embodiment, and includes a first substrate 110 / adhesion layer 10 / first functional stack 31 / first intermediate layer 51 / second functional stack 32 / second intermediate layer 52 / third functional stack 33 / third intermediate layer 53 / fourth functional stack 34 / first protective layer 711 / second protective layer 712 / outer protective layer 73 stacked in sequence. The first functional stack 31, the second functional stack 32, the third functional stack 33 and the fourth functional stack 34 all include a first dielectric layer 301, a metal layer 303 and a second dielectric layer 305.

[0118] The coated glass of comparative example 5 and the coated glass 100 of embodiments 9-11 were taken to measure the pencil hardness of the coated glass before and after heat treatment at 550°C to 720°C, and the test results of alcohol wiping are shown in Table 7. Among them, the traditional ZnSnO3 layer used in Table 7 is recorded as ZnSnO3 (MF), the ordinary ZnSnO3 layer is recorded as ZTO (MF), and the ceramic ZnSnO3 layer is recorded as ZTO (HiPIMS).

[0119] Table 7 Structure and test results of coated glass of Comparative Example 5 and Examples 9-11

[0120]

[0121]

[0122]

[0123] As can be seen from Table 7, in the coating structure of the coated glass of Comparative Example 5, MF power source is used to deposit ZnSnO3, and the obtained ZnSnO3 (MF) is used as the adhesion layer, the first intermediate layer, the second intermediate layer, the third intermediate layer and the second protective layer, and the pencil hardness test of the coating structure of Comparative Example 5 before and after heat treatment is 2H / HB respectively. In Examples 9-11, HiPIMS power source is used to supply instantaneous high power to the ZTO target, which not only promotes the ionization of the ZTO target to increase the sputtering rate, but also the prepared ZTO (HiPIMS) (i.e., ceramic ZnSnO3 layer) has the advantages of dense structure and smooth surface. Among them, Example 9 uses a ceramic ZnSnO3 layer as the adhesion layer 10, the first intermediate layer 51, the second intermediate layer 52, the third intermediate layer 53 and the second protective layer 712, Example 10 uses a ceramic ZnSnO3 layer as the first intermediate layer 51, the second intermediate layer 52 and the third intermediate layer 53, and Example 11 uses a ceramic ZnSnO3 layer as the first intermediate layer 51, the second intermediate layer 52, the third intermediate layer 53 and the second protective layer 712, and the obtained coating structure 130 has a higher film hardness.

[0124] The experimental results show that the use of the ceramic ZnSnO3 layer as the first intermediate layer 51 can improve the overall hardness of the coating structure 130, and as the adhesion layer 10 and / or the second protective layer 712 can further improve the overall hardness of the coating structure 130, so that the coating structure 130 has sufficient hardness to cope with various scratch challenges during deep processing. Among them, when the ceramic ZnSnO3 layer is used as the adhesion layer 10, the first intermediate layer 51, the second intermediate layer 52, the third intermediate layer 53 and the second protective layer 712 at the same time, the pencil hardness test of the coating structure 130 before / after heat treatment of Example 9 is respectively>9H / >9H, and the coating structure 130 has sufficient hardness to cope with various scratch challenges during deep processing.

[0125] Referring to Table 8, the process parameters and the performance after heat treatment of the coating structures of Comparative Examples 1-3 and Examples 1-2 are analyzed below.

[0126] Table 8 Process parameters and performance after heat treatment of the coating structures of Comparative Examples 1-3 and Examples 1-2

[0127]

[0128]

[0129] Among them, the film layers obtained by magnetron sputtering used in the coating structures 130 of Examples 3-5, the same film layers as those in Comparative Examples 1-3 and Examples 1-2 can refer to the data in Table 8, and are not listed here one by one. As can be seen from Table 8, in the coating structures 130 of Examples 1 and 2, the ZnSnO3 (ZTO) film layer (i.e., ceramic ZnSnO3 film layer) obtained by sputtering the ZTO target material using the HiPIMS power supply is used, and the sputtering rate of the ceramic ZnSnO3 film layer is increased by 61.5% to 115.4%. The increase in the sputtering rate is conducive to the application of the ceramic ZnSnO3 film material, and the cavity position, cathode, power supply, and molecular pump required for the application of the ceramic ZnSnO3 film material are reduced, thereby reducing the cost.

[0130] Referring to Table 9, the process parameters and the performance after heat treatment of the coating structures of Comparative Example 4 and Example 6 are analyzed below.

[0131] Table 9 Process parameters and performance after heat treatment of the coating structure of Comparative Example 4 and Example 6

[0132]

[0133] Among them, the film layers obtained by magnetron sputtering used in the coating structure 130 of Examples 7-8, the same film layers as those in Comparative Example 4 and Example 6 can refer to the data in Table 9, and are not listed here one by one. As can be seen from Table 9, in the coating structure 130 of Example 6, a ZnSnO3 (ZTO) film layer (i.e., a ceramic ZnSnO3 film layer) obtained by sputtering a ZTO target material using a HiPIMS power supply is used, and the sputtering rate of the ceramic ZnSnO3 film layer is increased by 61.5% to 115.4%. The increase in sputtering rate is conducive to the application of ceramic ZnSnO3 film materials, and the cavity positions, cathodes, power supplies, and molecular pumps required for the application of ceramic ZnSnO3 film materials are reduced, thereby reducing costs.

[0134] Referring to Table 10, the process parameters and the performance after heat treatment of the coating structures of Comparative Example 5 and Example 9 are analyzed below.

[0135] Table 10 Process parameters and performance after heat treatment of the coating structure of Comparative Example 5 and Example 9

[0136]

[0137] Among them, the film layers obtained by magnetron sputtering used in the coating structure 130 of Examples 10-11, the same film layers as those in Comparative Example 5 and Example 9 can refer to the data in Table 10, and are not listed here one by one. As can be seen from Table 10, in the coating structure 130 of Example 9, a ZnSnO3 (ZTO) film layer (i.e., a ceramic ZnSnO3 film layer) obtained by sputtering a ZTO target material using a HiPIMS power supply is used, and the sputtering rate of the ceramic ZnSnO3 film layer is increased by 61.5% to 115.4%. The increase in sputtering rate is conducive to the application of ceramic ZnSnO3 film materials, and the cavity positions, cathodes, power supplies, and molecular pumps required for the application of ceramic ZnSnO3 film materials are reduced, thereby reducing costs.

[0138] It can be seen from Tables 8-10 that, compared with the method of using MF power supply to magnetron sputter the film layer in the comparative example, the embodiment of the present application adopts HiPIMS power supply to replace the traditional MF power supply, and uses ZTO as the target material, which improves the sputtering rate of the film layer, thereby reducing the number of cathodes required for sputtering ZTO target materials using HiPIMS power supply. One cathode corresponds to one chamber position, one power supply, and several molecular pumps, thereby saving more costs.

[0139] The above experimental results show that the present embodiment of the application uses HiPIMS power to sputter ZTO target to obtain ZnSnO3 (ZTO) (i.e., ceramic ZnSnO3 film), and the sputtering rate of the ceramic ZnSnO3 film is increased by 61.5-115.4%. In addition, the ceramic ZnSnO3 film replaces the traditional ZnSnO3 film and the ordinary ZnSnO3 film in the coating structure 130, which can improve the overall hardness of the coating structure 130, so that the coated glass 100 has higher mechanical properties, so that it has sufficient hardness to resist various scratches during deep processing.

[0140] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A coated glass, characterized in that: The coated glass comprises: a first substrate; and A coating structure, wherein the coating structure is arranged on the first substrate, the coating structure comprises at least two functional stacks and at least one intermediate layer, the at least two functional stacks are sequentially stacked on the first substrate, and along a direction away from the first substrate, each of the functional stacks comprises a first dielectric layer, a metal layer, and a second dielectric layer which are sequentially stacked, the metal layer is arranged between the first dielectric layer and the second dielectric layer, the intermediate layer is arranged between two adjacent functional stacks, at least one of the intermediate layers comprises a ceramic ZnSnO3 layer, wherein the refractive index n value of the ceramic ZnSnO3 layer is 1.95 to 2.05, and the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0*10 -3 ~7.0*10 -3 .

2. The coated glass according to claim 1, characterized in that: The coating structure further includes an adhesion layer, which is disposed on the surface of the first substrate, and the at least two functional stacked layers are disposed on a side of the adhesion layer away from the first substrate.

3. The coated glass according to claim 2, characterized in that: The adhesion layer includes at least one of a SiAlZrNx layer, a ZrOx layer, a NbOx layer, a SiNx layer, a ZnSnOx layer, a SiZrNx layer and the ceramic ZnSnO3 layer.

4. The coated glass according to claim 2, characterized in that: The coating structure further includes a protective layer, which is disposed on a side of the at least two functional stacks away from the adhesion layer, and at least one of the adhesion layer and the protective layer includes the ceramic ZnSnO3 layer.

5. The coated glass according to claim 4, characterized in that: Along the direction away from the first substrate, the protective layer includes an inner protective layer and an outer protective layer, the inner protective layer is arranged on the side of the at least two functional stacks away from the adhesion layer, the outer protective layer is arranged on the side of the inner protective layer away from the at least two functional stacks, and the inner protective layer includes the ceramic ZnSnO3 layer.

6. The coated glass according to claim 5, characterized in that: The inner protective layer includes a first protective layer and a second protective layer, wherein the first protective layer is disposed on a side of the at least two functional stacks away from the adhesion layer, and the second protective layer is disposed between the first protective layer and the outer protective layer, wherein the second protective layer is the ceramic ZnSnO3 layer.

7. The coated glass according to claim 6, characterized in that: The material of the first protective layer is selected from oxides of at least one element among Zn, Mg, Sn, Ti, Nb and Zr.

8. The coated glass according to claim 5, characterized in that: The outer protective layer includes at least one of a SiAlZrNx layer, a SiZrNx layer, a ZrOx layer, a SiNx layer, a SiZrOx layer, and a SiAlZrOx layer.

9. The coated glass according to any one of claims 1 to 8, characterized in that: The first dielectric layer includes at least one of an AZO layer, a Ti alloy layer, a NbOx layer, a TiOx layer, a NiCr layer, a NiCrOx layer, a ZnAlOx layer, a ZnOx layer and a SnOx layer, and the second dielectric layer includes at least one of an AZO layer, a Ti alloy layer, a NbOx layer, a TiOx layer, a NiCr layer, a NiCrOx layer, a ZnAlOx layer, a ZnOx layer and a SnOx layer.

10. The coated glass according to any one of claims 1 to 8, characterized in that: The material of the metal layer includes any one of Ag, Au, Cu and Al or a metal alloy.

11. The coated glass according to any one of claims 1 to 8, characterized in that: There are two functional stacks, which include a first functional stack and a second functional stack. There is one intermediate layer, which is a first intermediate layer. The coating structure also includes a protective layer, which includes a first protective layer, a second protective layer and an outer protective layer. The coating structure includes an adhesion layer, the first functional stack, the first intermediate layer, the second functional stack, the first protective layer, the second protective layer and the outer protective layer, which are stacked in sequence. The first intermediate layer includes the ceramic ZnSnO3 layer.

12. The coated glass according to any one of claims 1 to 8, characterized in that: There are three functional stacks, which include a first functional stack, a second functional stack and a third functional stack. There are two intermediate layers, which include a first intermediate layer and a second intermediate layer. The coating structure also includes a protective layer, which includes a first protective layer, a second protective layer and an outer protective layer. The coating structure includes an adhesion layer, the first functional stack, the first intermediate layer, the second functional stack, the second intermediate layer, the third functional stack, the first protective layer, the second protective layer and the outer protective layer stacked in sequence. The first intermediate layer and the second intermediate layer both include the ceramic ZnSnO3 layer.

13. The coated glass according to any one of claims 1 to 8, characterized in that: The pencil hardness of the ceramic ZnSnO3 layer is ≥5H, and the pencil hardness of the coated glass after heat treatment is ≥7H.

14. A laminated glass, characterized in that: The method comprises a second substrate, an adhesive layer and the coated glass according to any one of claims 1 to 13, wherein the adhesive layer is bonded between the second substrate and the coated structure of the coated glass.

15. A method for preparing coated glass, characterized in that: include: providing a first substrate; A coating structure is prepared on the first substrate, the coating structure comprising at least two functional stacks and at least one intermediate layer, the at least two functional stacks are sequentially stacked on the first substrate, along a direction away from the first substrate, each of the functional stacks comprises a first dielectric layer, a metal layer and a second dielectric layer stacked sequentially, the metal layer is arranged between the first dielectric layer and the second dielectric layer, the intermediate layer is arranged between two adjacent functional stacks, at least one intermediate layer comprises a ceramic ZnSnO3 layer, wherein the refractive index n value of the ceramic ZnSnO3 layer is 1.95-2.05, and the extinction coefficient k value of the ceramic ZnSnO3 layer is 2.0*10 -3 ~7.0*10 -3 .

16. The method for preparing coated glass according to claim 15, characterized in that: The step of preparing a coating structure on the first substrate includes the step of preparing the ceramic ZnSnO3 layer: the target material is configured as a ZTO target material, a high-power pulsed magnetron sputtering power supply is used as the target power supply, the ZTO target material is magnetron sputtered to obtain the ceramic ZnSnO3 layer.

17. The method for preparing coated glass according to claim 16, characterized in that: The sputtering rate of the magnetron sputtering is 2.1 nm*m / (min*kW) to 2.8 nm*m / (min*kW).

18. The method for preparing coated glass according to claim 16, characterized in that: The peak power density of the magnetron sputtering was 14.47 W / cm 2 ~58.43W / cm 2 , the duty cycle is 5%~18%, and the pulse width is 30μs~60μs.

19. The method for preparing coated glass according to claim 16, characterized in that: The mass ratio of Zn:Sn in the ZTO target is 40:60 to 60:40.

Citation Information

Patent Citations

  • Low-radiation coated glass comprising two infrared reflecting layers and interlayer glass product of low-radiation coated glass

    CN106564242A

  • Head-up display glass and head-up display system

    CN117289468A

  • Coated glass, laminated glass and vehicle

    CN117720282A

  • Manufacture of ceramic superconducting laminate

    JP1995040493A

  • Windshield plate

    JP2022157905A